Boosting the Confidence of 1st Year College Students in Speaking Skills through Instructor’s Interactive Strategies during Face-to-Face Classes - Kevin Arabis, Karl; Tobio, Gabriel; Corpuz, Belen; Marie Royol, Bianca; T. Zita, Cris (Development: Studies in Educational Management and Leadership, 2023)
This study examines the significance of face-to-face classes as a venue for students and instructors to engage in teaching and learning activities in a shared physical space. The researchers employed a quantitative methodology for their study, with a sample size of 50 students from Holy Rosary College Foundation's 1st Year College cohort, which represented the entire population. Instruments for collecting data included interviews and survey questionnaires administered via pen-and-paper exams. The primary objective was to assess the efficacy of instructor-interactive strategies in traditional classroom settings. The findings revealed that various instructor-interactive strategies positively influenced the confidence levels of first-year college students, particularly in activities such as group work, class reporting, oral recitations, adherence to an English Only Policy (EOP), and role-playing exercises. In contrast, students viewed activities such as debates, memorization assignments, public speeches, impromptu speeches, and speech choir as less effective at boosting their speaking confidence. The study demonstrates that instructor-interactive strategies implemented in face-to-face classes have a positive effect on the speaking confidence of first-year college students. In the context of English language learning, these findings highlight the significance of incorporating interactive approaches into classroom instruction while taking individual student requirements into account. Throughout the teaching-learning process, instructors play a crucial role by actively participating in and collaborating on these interactive strategies.